Flow cytometric approach to evaluate endothelial function in patients with type 2 diabetes mellitus - P Kiruthika (2013)
Type 2 Diabetes mellitus is a metabolic disorder due to a condition known as insulin resistance. Endothelial dysfunction is one of the common complication in type 2 diabetes mellitus that is known to increase the risk of cardiovascular diseases. Endothelial progenitor cell types act as surrogate biomarkers for endothelial dysfunction. Circulating endothelial cells (CEC) and endothelial microparticles (EMP) are increased and endothelial progenitor cells (EPC) are decreased during endothelial dysfunction. Vitamin D deficiency has been associated with risk of cardiovascular diseases and literature shows evidence of vitamin D supplementation being helpful in reducing the risk of vascular damage. This study involved coming up with an accurate and standard protocol for the quantification of cellular markers such as the CEC, EMP and EPC in fresh whole blood. Flow cytometry along with a four color staining protocol was used to enumerate the levels of EPC, CEC and EMP in blood obtained from 49 patients with type 2 diabetes mellitus from Tan Tock Seng Hospital, Singapore. The results obtained were analyzed in collaboration that showed that there was a clear relationship between endothelial cell count and endothelial function, however not enough data was acquired to conclude the relationship between vitamin D levels and endothelial function in this preliminary study.